2017
DOI: 10.1007/s10995-016-2259-7
|View full text |Cite
|
Sign up to set email alerts
|

Is Perceived Discrimination in Pregnancy Prospectively Linked to Postpartum Depression? Exploring the Role of Education

Abstract: Objectives The role of perceived discrimination in postpartum depression is largely unknown. We investigate whether perceived discrimination reported in pregnancy contributes to postpartum depression, and whether its impact varies by education level. Methods Prospective data are a part of European Longitudinal Study of Pregnancy and Childhood, the Czech Republic. Surveys were collected in mid-pregnancy and at 6 months after delivery. Depression was measured using Edinburgh Postnatal Depression Scale. Generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 66 publications
3
8
0
2
Order By: Relevance
“…We identified perceived discrimination as a strong predictor of depressive symptoms during pregnancy. This finding is consistent with previous research conducted among pregnant women in the Czech Republic which showed that perceived discrimination was associated with increased odds of postpartum depression [37]. Similarly, a population-based study of young (ages [18][19][20] women in the Midwest region of the U.S. found a positive association between discrimination and depressive symptoms [38].…”
Section: Plos Onesupporting
confidence: 91%
“…We identified perceived discrimination as a strong predictor of depressive symptoms during pregnancy. This finding is consistent with previous research conducted among pregnant women in the Czech Republic which showed that perceived discrimination was associated with increased odds of postpartum depression [37]. Similarly, a population-based study of young (ages [18][19][20] women in the Midwest region of the U.S. found a positive association between discrimination and depressive symptoms [38].…”
Section: Plos Onesupporting
confidence: 91%
“…In a population of British women, it showed relative stability between pregnancy and years eight to eleven postpartum and a slight increase between years eleven and eighteen [35]. EPDS has been used in high-, middle-, and low-income countries, including the Czech Republic [36][37][38][39][40][41]. The present study used EPDS scores collected at baseline (midpregnancy), after delivery, at child age six months, eighteen months, three years, five years, seven years, and eleven years.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…Previous research, mainly from Western countries (the US, Europe or New-Zealand), showed that discrimination is associated with increased risk of health problems during pregnancy and after birth [26], including postpartum depression (PPD) [2729]. PPD is a serious public health issue faced by almost one fifth of new mothers in Western countries [30] and up to two thirds in non-Western countries [31].…”
Section: Introductionmentioning
confidence: 99%